JEJARING KEBIJAKAN BNPT DALAM SINERGITAS PROGRAM DERADIKALISASI - Taufiqurochman, Muhammad (Journal of Terrorism Studies, 2021)
BNPT has a main task and function, one of which is to realize national coordination, strategy and programs in the field of counter-terrorism. To organize inter-institutional coordination, it is necessary to collaborate on policy networks or synergies. All stakeholder policy makers must take sides in counter-terrorism efforts. In this case, BNPT is the leading sector (Core) in coordinating between law enforcement institutions, institutions and the community to create synergy. The importance of synergy between Ministries/Agencies can increase the capacity and capability of the government's performance in dealing with threats and challenges in countering terrorism. Combating crime is not only the responsibility of law enforcement institutions, but also the responsibility of every non-law enforcement institution to continue to synergize in all efforts to de-radicalize, counter radicalization, and develop relationship facilities through a soft approach from upstream to downstream. The research uses qualitative methods, by reviewing credible data sources by conducting observations, in-depth interviews and documents. The results of this study indicate that deradicalization within the correctional facility with the methods of identification, rehabilitation, reeducation, resocialization and deradicalization outside the correctional institution (Society) with the method of fostering national insight, fostering religious insight and fostering entrepreneurship supported by the synergy of all stakeholders is a systematic, planned and integrated program.